FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI PADA KELOMPOK TANI PATEMON II DI DESA PATEMON KECAMATAN TLOGOSARI KABUPATEN BONDOWOSO - Kiki Diantoro; M. Sunarsih; Djoko Soejono (University of Jember, 2009)
The determination of research area is done using purposive method in Patemon Village Tlogosari Sub district Bondowoso Regency. The method applied in this research are analytic and descriptive method. The sampling method is done using disproportionate stratified random sampling method and the Gay’s theory. The data applied in this research are primary and secondary data. This research is aim to knows: (1) the earnings of rice farming at Patemon II farmer group, (2) the rice farming production cost efficiency at Patemon II farmer group, (3) factors that influencing the produce of rice farming at Patemon II farmer group. The research result shows: (1) the earnings of rice farming at Patemon II farmer group are profit, (2) the usage of rice farming production cost at Patemon II farmer group is efficient, and (3) Factors that have an effect on the produce of rice farming at Patemon II farmer group are fertilizer, drugs, and labor.Key words: rice, earnings, cost efficiency.